Häufigkeit von Zahn-, Mund- und Kieferverletzungen und Bewährung von Mundschutzen bei Spitzensportlern - Bemelmanns, P.; Pfeiffer, P. (Sportverletzung Sportschaden, 2000)
The aim of the study was to determine the prevalence of orofacial injuries among German top athletes and their attitudes to mouthguards. A questionnaire was mailed to athletes of 10 German contact sports associations. 64.3 percent (303) of the athletes returned questionnaires. 62 percent (188) of the respondents reported that at some time they wore a mouthguard for sports participation. 47.3 % (male: 57.8 %, female: 38.3 %) of these were currently using one. 50 % of the mouthguards were custom made by dentists, and 50 % were shop bought (boil-and-bite). 32 percent of the participants had, at some time during their sports career, suffered an orofacial injury. The incidence of fractured anterior upper teeth and completely knocked out teeth for athletes without mouthguards was 7 and 14, respectively. Whereas for athletes wearing mouthguards one fractured tooth was reported. Athletes with mouthguards complained of problems with speaking (19.9 %) rather than of breathing (3.4 %) and fitting difficulties (4.8 %). Boil-and-bite mouthguards caused more fitting problems than custom-made ones. As prevalence of oral injuries in body-contact sports is high, athletes should be advized that custom-made mouthguards offer the greatest comfort, fit, durability, and protection against dental injuries.